The role of tolvaptan in pulmonary hypertension: A retrospective study. Issue 47 (25th November 2022) - Chen, Qiaoli; Luo, Heng; Li, Yuping
Abstract : Pulmonary hypertension (PH) is a severe form of pulmonary vascular disease that can lead to right heart failure (RHF). Nearly 2-thirds of patients with PH die within 5 years. Studies suggest that a new diuretic medication, called tolvaptan (TLV), can be used to treat PH. However, there is still insufficient evidence to confirm its effectiveness. Therefore, we investigated the role of TLV in patients with PH. This retrospective study included 73 patients with PH hospitalized in Shanghai Pulmonary Hospital between November 2019 and March 2022. All patients received 7.5 to 15.0 mg of TLV for 3 to 21 days starting at admission, in addition to targeted drugs and traditional diuretic therapy. The outcomes included the blood pressure, urine and water intake volumes, electrolyte concentrations, and renal, liver, and cardiac function indexes before and after TLV treatment. In addition, we assessed the clinical symptoms and adverse reactions during the treatment. After TLV treatment, the water intake and urine volumes significantly increased, and body weight, diastolic blood pressure (DBP) and mean arterial pressure significantly decreased. Total bilirubin, direct bilirubin, N-terminal pro-brain natriuretic peptide, and serum uric acid (UA) levels after TLV treatment were significantly lower than before treatment. After TLV treatment, dyspnea significantly improved in 71 of 73 patients, and lower limb edema disappeared in 42 of 53 patients. No obvious adverse reactions occurred during the TLV treatment period. These results suggest that adding TLV to targeted drug and traditional diuretic therapies is effective for patients with PH. However, more data are required to support these findings.